To Report or Not to Report? A Focal Concerns Analysis of Victim Reporting Decisions Following Victimization - Kelley, Shamika M. (Journal of interpersonal violence, 2022)
Sexual assault (SA) decision-making literature primarily focuses on criminal-legal actors and often overlooks victim decision making. This relative dearth in research is problematic, as victims are principal gatekeepers of the criminal-legal process who influence whether perpetrators are arrested and prosecuted. Subsequent victim support is also contingent on the reporting decision. Overall, this body of research would benefit from a better understanding of how victims activate and participate with the criminal-legal system and the potential impact of these decisions on criminal-legal processes. Moreover, victim decision making is often situated in a theoretical analyses. Victim decision making is complex and should be studied within a criminological decision-making framework. Therefore, the current study relies on National Crime Victimization Survey (NCVS) data and applies a focal concerns perspective (FCP), informed by rape culture concepts, to examine why victims of sexual violence may or may not choose to report to legal authorities. The current study offers initial support for the application of FCP to victim reporting decisions. We found that victims consider each of the focal concerns (FC). Victims were more likely to report when offenders threatened them with harm (i.e., suspect blameworthiness), when the offense occurred in a private location (i.e., protection of the community), and when they sought help from victim support agencies or medical treatment (i.e., practical considerations). Additionally, we found that Black victims were more likely to report than other racial-ethnic groups (i.e., perceptual shorthand). These findings highlight a nexus between reporting to police and help-seeking via support agencies. Importantly, the results emphasize the importance for police to implement cultural competence and antiracist training to better support Black victims.